Comparison of supine and seated orthostatic hypotension assessments and their association with falls and orthostatic symptoms. Issue 8 (22nd April 2022) - Juraschek, Stephen P.; Appel, Lawrence J.; M. Mitchell, Christine; Mukamal, Kenneth J.; Lipsitz, Lewis A.; Blackford, Amanda L.; Cai, Yurun; Guralnik, Jack M.; Kalyani, Rita R.; Michos, Erin D.; Schrack, Jennifer A.; Wanigatunga, Amal A.; et al.
Abstract: Background: Orthostatic hypotension (OH) based on a change from seated‐to‐standing blood pressure (BP) is often used interchangeably with supine‐to‐standing BP. Methods: The Study to Understand Fall Reduction and Vitamin D in You (STURDY) was a randomized trial of vitamin D3 supplementation and fall in adults aged ≥70 years at high risk of falls. OH was defined as a drop in systolic or diastolic BP of at least 20 or 10 mmHg, measured at pre‐randomization, 3‐, 12‐, and 24‐month visits with each of 2 protocols: seated‐to‐standing and supine‐to‐standing. Participants were asked about orthostatic symptoms, and falls were ascertained via daily fall calendar, ad hoc reporting, and scheduled interviews. Results: Among 534 participants with 993 paired supine and seated assessments (mean age 76 ± 5 years, 42% women, 18% Black), mean baseline BP was 130 ± 19/68 ± 11 mmHg; 62% had a history of high BP or hypertension. Mean BP increased 3.5 (SE, 0.4)/2.6 (SE, 0.2) mmHg from sitting to standing, but decreased with supine to standing (mean change: −3.7 [SE, 0.5]/−0.8 [SE, 0.3] mmHg; P ‐value < 0.001). OH was detected in 2.1% (SE, 0.5) of seated versus 15.0% (SE, 1.4) of supine assessments ( P  < 0.001). While supine and seated OH were not associated with falls (HR: 1.55 [0.95, 2.52] vs 0.69 [0.30, 1.58]), supine systolic OH was associated with higher fall risk (HR: 1.77 [1.02, 3.05]). Supine OH was associated with self‐reported fainting, blacking out, seeing spots and room spinning in the prior month ( P ‐values < 0.03), while sitting OH was not associated with any symptoms ( P ‐values ≥ 0.40). Conclusion: Supine OH was more frequent, associated with orthostatic symptoms, and potentially more predictive of falls than seated OH.